Things we keep behind glass visualization of familial ideas in a middle-class Filipino family - Galeno, Renee Francesca M.
Although there exists an ideal family structure in every culture, there are very few families that fit into that mold. As is the case with my own family, one that is far from the idealized, traditional Catholic family aspired to by Filipino culture. This work attempts to dissect the constructed facade of a family through the appropriation of the items found in that family's china cabinet. Based on Edward Hall's notion of interpersonal distance, the work simulates an encounter with a family. As the viewer navigates through the space, the narrative within the cabinet and thus the narrative of the family, is made more apparent. The work also explores the expressive nature of the sensory home, the cultural habitus that informs this, and its ability to represent its inhabitants.